Analysis of in vitro expression of virulence genes related to antibiotic and disinfectant resistance in Escherichia coli as an emerging periodontal pathogen - Monroy-Pérez, Eric; Hernández-Jaimes, Tania; Morales-Espinosa, Rosario; Delgado, Gabriela; Martínez-Gregorio, Héctor; García-Cortés, Luis Rey; Herrera-Gabriel, Jennefer Paloma; De Lira-Silva, Andrea; Vaca-Paniagua, Felipe; Paniagua-Contreras, Gloria Luz (Frontiers in Cellular and Infection Microbiology, 2024)
The collective involvement of virulence markers of Escherichia coli as an emerging pathogen associated with periodontitis remains unexplained. This study aimed to implement an in vitro model of infection using a human epithelial cell line to determine the virulome expression related to the antibiotic and disinfectant resistance genotype and pulse field gel electrophoresis (PFGE) type in E. coli strains isolated from patients with periodontal diseases. We studied 100 strains of E. coli isolated from patients with gingivitis (n = 12), moderate periodontitis (n = 59), and chronic periodontitis (n = 29). The identification of E. coli and antibiotic and disinfectant resistance genes was performed through PCR. To promote the expression of virulence genes in the strains, an in vitro infection model was used in the human epithelial cell line A549. RNA was extracted using the QIAcube robotic equipment and reverse transcription to cDNA was performed using the QuantiTect reverse transcription kit (Qiagen). The determination of virulence gene expression was performed through real-time PCR. Overall, the most frequently expressed adhesion genes among the isolated strains of gingivitis, moderate periodontitis, and chronic periodontitis were fimH (48%), iha (37%), and papA (18%); those for toxins were usp (33%); those for iron acquisition were feoB (84%), fyuA (62%), irp-2 (61%), and iroN (35%); those for protectins were traT (50%), KpsMT (35%), and ompT (28%); and those for pathogenicity islands were malX (45%). The most common antibiotic and disinfectant resistance genes among gingivitis, moderate periodontitis, and chronic periodontitis strains were sul-2 (43%), blaSHV (47%), blaTEM (45%), tet(A) (41%), dfrA1 (32%), marR-marO (57%), and qacEA1 (79%). The findings revealed the existence of a wide distribution of virulome expression profiles related to the antibiotic and disinfectant resistance genotype and PFGE type in periodontal strains of E. coli. These findings may contribute toward improving the prevention and treatment measures for periodontal diseases associated with E. coli.